Ecology of Mudskippers in Kampung Pasir Putih, Sarawak - Naquiah, binti Abdul Ghani (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The study of ecology of mudskipper was conducted in Kpg. Pasir Putih, Sarawak at intertidal zone of mangrove area. Thirty-five samples of mudskippers were collected by using scoop net and by hands with the aid from local fisherman. The total lengths were ranged from 3.4 to 8.0 cm and there was a very strong correlation between total length and weight of mudskippers (r=0.968). The species of mudskippers were identified as Periophthalmus chrysospilos. The distribution of mudskippers in Kpg. Pasir Putih, Sarawak was influenced by dissolved oxygen, pH, salinity, temperature, total organic matter and particle size. Based on particle size analysis, about 80-90% of sediment was silt and clay, whereas 10-20% was sand. There was strong negative correlation (r=-0.763) and (r=-0.625) between TOM with dissolved oxygen and temperature respectively, whereas there was strong positive correlation (r=0.645) between dissolved oxygen and pH value of water parameters. The distribution of juvenile mudskippers was the highest at plot 3 compared to plot 1 and 2 in Kampung Pasir Putih, Sarawak.